Two New Mechanisms of Macrolide Resistance in Clinical Strains of Streptococcus pneumoniae from Eastern Europe and North America - Tait-Kamradt, A. (American Society for Microbiology, 2000)
Resistance to macrolides in pneumococci is generally mediated by methylation of 23S rRNA via erm(B) methylase which can confer a macrolide (M)-, lincosamide (L)-, and streptogramin B (S(B))-resistant (MLS(B)) phenotype or by drug efflux via mef(A) which confers resistance to 14- and 15-membered macrolides only. We studied 20 strains with unusual ML or MS(B) phenotypes which did not harbor erm(B) or mef(A). The strains had been isolated from patients in Eastern Europe and North America from 1992 to 1998. These isolates were found to contain mutations in genes for either 23S rRNA or ribosomal proteins. Three strains from the United States with an ML phenotype, each representing a different clone, were characterized as having an A2059G (Escherichia coli numbering) change in three of the four 23S rRNA alleles. Susceptibility to macrolides and lincosamides decreased as the number of alleles in isogenic strains containing A2059G increased. Sixteen MS(B) strains from Eastern Europe were found to contain a 3-amino-acid substitution ((69)GTG(71) to TPS) in a highly conserved region of the ribosomal protein L4 ((63)KPWRQKGTGRAR(74)). These strains formed several distinct clonal types. The single MS(B) strain from Canada contained a 6-amino-acid L4 insertion ((69)GTGREKGTGRAR), which impacted growth rate and also conferred a 500-fold increase in MIC on the ketolide telithromycin. These macrolide resistance mechanisms from clinical isolates are similar to those recently described for laboratory-derived mutants.